Understanding the ‘Shadow Economy’ in SMES – a Malpractice from Indonesia, 2009-2020 - Diana Lestari; Syarifah Hudayah; Arfiah Busari (Media Ekonomi dan Manajemen, 2022)
Concerns about the shadow economy in Indonesia, estimated to have hurt GDP by around 25% per year. We try to calculate the effect of the components involved in tax revenue caused by the shadow economy because we projected it to hinder the growth of SMEs. It aimed the orientation at Indonesia. We got data coverage from official institutions of national and international related to variable limits. We observe the development in the period 2009-2020, which requires linear regression analysis methods and non-linear logistic regression. The results confirm that among the six hypotheses we propose, five hypotheses are acceptable, i.e. FDI has a significant effect on the share of SMEs, corruption perceptions and control of corruption have a significant effect on income and profit taxes, then it also has a significant effect on the shadow economy, and the shadow economy also has an effect significant to tax revenue. From other findings, only the share of SMEs has no significant effect on income and profit taxes. The added value of this empirical finding can reduce the weaknesses of previous studies that predominantly consider financial (tax) and economic dimensions so that variables such as SMEs, corruption control, and public perceptions of corruption.